2017
DOI: 10.1111/acps.12823
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric asymmetry of the frontolimbic cortex in young adults with borderline personality disorder

Abstract: Patients with BPD have greater frontolimbic asymmetry than healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Additionally, atypically high functional connectivity between the precuneus and frontal lobes has been found to be related to hyperactive processing of internal thoughts and self-referential information in BPD ( 19 ). Our research group has also found several BPD-related structural and functional brain anomalies, including enlarged GMVs of the right PCC and precuneus with resting-state (rs) brain hypoactivity ( 11 , 20 ), disrupted white matter integrity and functional connectivity of the frontal medial cortex ( 20 , 21 ), and augmented asymmetry and disturbed resting-state functional connectivity of the frontolimbic cortex ( 20 , 22 ).…”
Section: Introductionmentioning
confidence: 77%
“…Additionally, atypically high functional connectivity between the precuneus and frontal lobes has been found to be related to hyperactive processing of internal thoughts and self-referential information in BPD ( 19 ). Our research group has also found several BPD-related structural and functional brain anomalies, including enlarged GMVs of the right PCC and precuneus with resting-state (rs) brain hypoactivity ( 11 , 20 ), disrupted white matter integrity and functional connectivity of the frontal medial cortex ( 20 , 21 ), and augmented asymmetry and disturbed resting-state functional connectivity of the frontolimbic cortex ( 20 , 22 ).…”
Section: Introductionmentioning
confidence: 77%
“…Deficits in affective and cognitive brain functions and alterations in emotion-attention interaction are seen in psychiatric, neurodegenerative and neurodevelopmental disorders. Abnormal brain lateralization has been reported, for example, in schizophrenia [19,20], borderline personality disorder (BPD) [149], FTD [33] and ADHD [150], and is thought to account for some of the cognitive and affective deficits and social challenges linked with these disorders. Hypo-or hyperactivity or alteration in normal activity balance between the two hemispheres is reflected in FAA, and alteration in emotion-attention interaction likely reflected in the novel eFAA index.…”
Section: Emotional Modulation Of Faa-a Novel Biomarker For Rh Emotion-attention Interactionmentioning
confidence: 99%
“…Notably, preterm birth leads to alterations in the fronto-striatal and temporal lobes, and the development of the limbic region takes place in a critical period of fetal brain development. The fronto-limbic pathway primarily consists of the orbitofrontal, the anterior cingulate, insula, and limbic regions, including the amygdala and hippocampus, which is known as the brain’s affective network, underlying the processing and regulation of emotions [ 14 , 15 , 16 ]. The impact of prematurity on cerebral development and damage has been extensively studied using magnetic resonance imaging (MRI) [ 17 ], which provides sensitive assessments of abnormal morphology and microstructure that correspond with neurodevelopmental outcomes [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%